2008
DOI: 10.1002/da.20346
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms and brain function during a response-inhibition task: an fMRI study in youth

Abstract: Youth who experience interpersonal trauma and have posttraumatic stress symptoms (PTSS) can exhibit difficulties in executive function and physiological hyperarousal. Response inhibition has been identified as a core component of executive function. In this study, we investigate the functional neuroanatomical correlates of response inhibition in youth with PTSS. Thirty right-handed medication-naïve youth between the ages of 10 and 16 years underwent a 3-Tesla Functional Magnetic Resonance Imaging scan during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
147
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(159 citation statements)
references
References 77 publications
9
147
0
3
Order By: Relevance
“…This suggests that diminished middle frontal activity and enhanced medial frontal activity during response-inhibition tasks may represent both a neurofunctional marker and a pathophysiological mechanism of development for PTSS. Furthermore, we also found that within the group of children with PTSS, children with self-injurious behaviors had increased insula and orbitofrontal activation compared with children without self-injurious behaviors, with greater insula activation correlated to greater PTSS severity [26]. By implicating a self-injurious subtype of PTSD that may represent a failure of response inhibition associated with more severe PTSS and greater insula activation, this finding suggests that neuroimaging may further our understanding of the heterogeneity in PTSD by identifying clinically relevant biological subtypes.…”
Section: The Prefrontal Cortexmentioning
confidence: 79%
See 1 more Smart Citation
“…This suggests that diminished middle frontal activity and enhanced medial frontal activity during response-inhibition tasks may represent both a neurofunctional marker and a pathophysiological mechanism of development for PTSS. Furthermore, we also found that within the group of children with PTSS, children with self-injurious behaviors had increased insula and orbitofrontal activation compared with children without self-injurious behaviors, with greater insula activation correlated to greater PTSS severity [26]. By implicating a self-injurious subtype of PTSD that may represent a failure of response inhibition associated with more severe PTSS and greater insula activation, this finding suggests that neuroimaging may further our understanding of the heterogeneity in PTSD by identifying clinically relevant biological subtypes.…”
Section: The Prefrontal Cortexmentioning
confidence: 79%
“…In a functional study (functional MRI [fMRI]) of brain activation during a response-inhibition task, we studied 16 children with PTSS in comparison with 14 healthy children [26]. We found that children with PTSS showed reduced middle frontal cortex and increased left medial frontal gyrus and anterior cingulate gyrus activation compared with healthy control subjects during a response-inhibition task.…”
Section: The Prefrontal Cortexmentioning
confidence: 97%
“…These pathways center around 1), reduced cognitive control and self-regulatory abilities and 2), dysfunctional emotion processing. Although limited, on the one hand, previous work in individuals with experience of ES has documented impairments in cognitive control such as inhibition (Carrion, Garrett, Menon, Weems, & Reiss, 2008;De Bellis, Hooper, Spratt, & Woolley, 2009;Jovanovic et al, 2012;Lewis, Dozier, Ackerman, & Sepulveda-Kozakowski, 2007;Mueller et al, 2012), response shifting (Mueller et al, 2010), and working memory (Majer, Nater, Lin, Capuron, & Reeves, 2010).…”
mentioning
confidence: 99%
“…Due to the frequent co-occurrence of multiple stressors (J. G. Green et al, 2010), most of these previous studies have included individuals with different types of early-life stress, such as neglect and maltreatment (Mueller et al, 2010), emotional abuse, sexual or physical abuse and/or neglect (Majer et al, 2010) and youth who experienced physical or sexual abuse, or witnessed violence (Carrion et al, 2008). By comparison, only a few of these studies have differentiated between types of stressors and have taken the severity of the early-stress experience into account (De Bellis et al, 2009;Majer et al, 2010).…”
mentioning
confidence: 99%
“…In children, emotion regulation has been linked to emotional and behavioral problems as well as positive competencies (e.g., Eisenberg et al 1996Eisenberg et al , 1998Eisenberg et al , 2007aKochanska and Knaack 2003;Riggs et al 2003;Silk et al 2003;Spinrad et al 2006Spinrad et al , 2007. Prolonged emotional dysregulation (e.g., hyperarousal associated with traumatic stress) is associated with hormonal dysregulation, academic difficulties, as well as structural brain changes and functional deficits in youth (e.g., Carrión et al 2007Carrión et al , 2008; De Bellis 2001;Weems and Carrión 2007).…”
mentioning
confidence: 99%